2010
DOI: 10.1021/la100231u
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Energy Engineering of Graphene

Abstract: Contact angle goniometry is conducted for epitaxial graphene on SiC. Although only a single layer of epitaxial graphene exists on SiC, the contact angle drastically changes from 69 degrees on SiC substrates to 92 degrees on graphene. It is found that there is no thickness dependence of the contact angle from the measurements of single-, bi-, and multilayer graphene and highly ordered pyrolytic graphite (HOPG). After graphene is treated with oxygen plasma, the level of damage is investigated by Raman spectrosco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
369
4
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 445 publications
(400 citation statements)
references
References 32 publications
25
369
4
2
Order By: Relevance
“…The increase in adhesion was attributed to the creation of dangling bonds due to plasma treatment, which in turn acted as surface charge traps. This results were consistent with the findings of Shin et al 101 They determined that the defects created due to plasma treatment changed graphene form hydrophobic to hydrophilic. Using Raman spectroscopy and water contact angle measurements they were able to correlate degree of disorder with wettability.…”
Section: Nitrogen Functionalizationsupporting
confidence: 93%
“…The increase in adhesion was attributed to the creation of dangling bonds due to plasma treatment, which in turn acted as surface charge traps. This results were consistent with the findings of Shin et al 101 They determined that the defects created due to plasma treatment changed graphene form hydrophobic to hydrophilic. Using Raman spectroscopy and water contact angle measurements they were able to correlate degree of disorder with wettability.…”
Section: Nitrogen Functionalizationsupporting
confidence: 93%
“…The contact angle θ is taken as that of a water droplet on graphite [20,21], approx. 90 The surface tension force of eq.…”
Section: The Surface Tension Force At the Contact Linementioning
confidence: 99%
“…The interaction of the interfacial water with EG grown on SiC has been studied theoretically [18,19] and experimentally by frequency modulation AFM [20], highresolution X-ray analyses [21], vibrational spectroscopy [22], and contact angle goniometry [23]. It has been shown that the G 0 containing high number of sp 3 carbon-bonded inclusions chemically bonds the closest lying water molecules and, probably, blocks electrochemical reactions at the interface.…”
Section: Introductionmentioning
confidence: 99%